PEMBUATAN APLIKASI TP4D KEJAKSAAN NEGERI PURWOKERTO BERBASIS ANDROID - Imam Fadlilah, Nuzul; - UBSI Banyumas, Okvi Dwi Santra (APMMI - Asosiasi Profesi Multimedia Indonesia, 2020)
Abstract - The Purwokerto District Attorney's Office is a government agency under the auspices of the Attorney General's Office of the Republic of Indonesia, the implementation of duties and authorities related to the investigation, prosecution of cases of corruption and gross violations of human rights, as well as other authorities based on applicable law. In an effort to carry out their duties in preventing the occurrence of criminal acts of corruption in the environment of government agencies in the form of the Government and Development Guard and Security Team (TP4) for the central level and the Government and Regional Guard and Security Team (TP4D) for the regional level. This formation is based on the Indonesian Attorney General's Decree Number: KEP-152/A/JA/10/2015 on October 01, 2015. The establishment of TP4D aims to provide legal escort and information within the local government agencies and BUMD in addition to eliminating doubts about the state apparatus in making a decision, maximum absorption of the regional budget, the realization of bureaucratic improvements and acceleration of national strategic programs for the benefit of the people, encourage national economic growth and development, and implementing effective law enforcement by prioritizing prevention efforts. In carrying out their duties, they conduct escort and legal information, The TP4D of the Purwokerto District Attorney's Office has obstacles in conducting data collection on activities such as the difficulty of documenting activities, mapping activities that are not clear and where the location of their activities are as well as the presentation of information to the applicant for the activities (Local Government Agencies and BUMD) that are lacking. To help the Purwokerto District Attorney's TP4D in carrying out its duties in providing escort, a TP4D application was aimed at facilitating the team in carrying out data collection activities and providing easy access in obtaining activity information to applicants. Keywords: Task, TP4D, Prevention, Corruption, Prosecutor's Office Abstrak - Kejaksaan Negeri Purwokerto merupakan instansi pemerintah dibawah naungan Kejaksaan Agung Republik Indonesia, yang pelaksanaan tugas dan kewenangannya terkait dengan penyidikan, penuntutan perkara tindak pidana korupsi dan pelanggaran HAM berat, serta kewenangan lain berasaskan undang-undang yang berlaku. Dalam upaya melaksanakan tugasnya dalam mencegah terjadinya tindak pidana korupsi di lingkungan instansi pemerintahan maka di bentuk Tim Pengawal dan Pengaman Pemerintahan dan Pembangunan (TP4) untuk tingkat pusat dan Tim Pengawal dan Pengaman Pemerintahan dan Pembangunan Daerah (TP4D) untuk tingkat daerah. Pembentukan ini berdasarkan SK Jaksa Agung RI Nomor : KEP-152/A/JA/10/2015 pada 01 Oktober 2015. Pembentukan TP4D bertujuan untuk memberikan pengawalan dan penerangan hukum di lingkungan instansi pemerintahan daerah dan BUMD selain itu untuk menghilangkan keraguan aparatur negara dalam mengambil sebuah keputusan, terserapnya anggaran daerah secara maksimal, terwujudnya perbaikan birokrasi dan percepatan program-program strategis nasional untuk kepentingan rakyat, mendorong pertumbuhan ekonomi dan pembangunan nasional, serta melaksanakan penegakan hukum yang efektif dengan mengutamakan upaya pencegahan. Dalam pelaksanaan tugasnya melakukan pengawalan dan penerangan hukum, TP4D Kejaksaan Negeri Purwokerto memiliki kendala dalam melakukan pendataan informasi kegiatan seperti sulitnya mendokumentasikan kegiatan, mapping kegiatan yang tidak jelas dan dimana letak lokasi kegiatannya serta penyajian informasi kepada pemohon kegiatan (Instansi Pemerintah Daerah dan BUMD) yang kurang. Untuk membantu TP4D Kejaksaan Negeri Purwokerto dalam melakukan tugasnya dalam memberikan pengawalan maka dibangun aplikasi TP4D tujuannya mempermudah tim dalam melakukan pendataan kegiatan serta memberikan kemudahan akses dalam memperoleh informasi kegiatan kepada pemohon. Kata Kunci : Tugas, TP4D, Pencegahan, Korupsi, Kejaksaan.